Система передачи цифровой информации на основе многоуровневых сигналов с компактным спектром - Sukachоv, E. A.; Shkulipa, P. A. (PE "Politekhperiodika", Book and Journal Publishers, 2008)
A method for digital information transmission is proposed that reduces intersymbol interference and improves the efficiency of clock synchronization devices through the use of specially shaped signal functions. Analytical expressions have been obtained for multilevel signal functions and their compact spectra. A structural scheme implementing the proposed method has been developed, and the properties of its individual elements are described.